Nanomaterials as a game changer in the management and treatment of diabetic foot ulcers. Issue 115 (12th December 2016) - Vellayappan, M. V.; Jaganathan, S. K.; Manikandan, A.
Abstract : Nanoengineered biomaterials have tremendously improved the range of tools utilized for the control of as well as acceleration of healing of diabetic foot ulcers (DFU) over the last few decades. Abstract : Nanoengineered biomaterials have tremendously improved the range of tools utilized for the control of as well as acceleration of healing of diabetic foot ulcers (DFU) over the last few decades. Despite nanoparticles and electrospun nanofibers being used extensively for the treatment of DFU, there has been no review available till now which addresses the utilization of the latest nanodelivery techniques along with modern electrospun nanofiber treatments for DFU. This review thoroughly summarizes the latest mindboggling findings of potential nanomaterials like polymeric and metallic nanoparticles and electrospun nanofibers for DFU treatment. In addition, a succinct insight into the potential of the aforementioned nanomaterials which can be exploited as therapeutic delivery agents for improving the regeneration of damaged dermal and epidermal tissues of DFU is underscored. Ultimately, current challenges and future prospects of nanoparticles and electrospun nanofibers for DFU treatment are highlighted.